Liposome-mediated small RNA delivery to convert the macrophage polarity: A novel therapeutic approach to treat inflammatory uterine disease - Mira Park; Hyeon-Ji Oh; Jieun Han; Seok-Ho Hong; Wooram Park; Haengseok Song (Molecular Therapy: Nucleic Acids, 2022)
Macrophages are present in all tissues for maintaining tissue homeostasis, and macrophage polarization plays a vital role in alleviating inflammation. Therefore, specific delivery of polarization modulators to macrophages in situ is critical for treating inflammatory diseases. We demonstrate that a size-controlled miRNA-encapsulated macrophage-targeting liposomes (miR/MT-Lip) specifically targets macrophages to promote M1-to-M2 polarization conversion, alleviating inflammation without cytotoxicity. miR/MT-Lip, approximately 1.2 μm, showed excellent internalization through phagocytosis and/or macropinocytosis in macrophages. miR-10a/MT-Lip, but not scramble miR-Fluorescein amidite (FAM)/MT-Lip as control, effectively converted the polarization of lipopolysaccharide (LPS)-induced M1 macrophages to M2 in vitro. When miR-10a/MT-Lip was intravenously delivered to mice insulted with LPS for inflammation, the proportion of M2 macrophages was significantly increased without disturbing the population of other immune cells. Furthermore, scramble miR-FAM/MT-Lip was mainly detected in macrophages, but not other immune cells. When our miR/MT-Lip was administered to mice with Asherman’s syndrome that suffer from infertility because of sterile uterine inflammation, macrophage-specific targeting of miR-10a/MT-Lip facilitated M1-to-M2 conversion for angiogenesis in the impaired uterus, resulting in restoration of healthy uterine conditions. The results indicate that our MT-Lip encapsulating small RNAs has excellent potential to treat various inflammatory disorders by fine-tuning macrophage polarization in vivo without any side effects.